Top management: the missing stakeholder in the HRM literature. Issue 1 (2nd January 2019) - Boada-Cuerva, Maria; Trullen, Jordi; Valverde, Mireia
Abstract: Despite the significant influence that top management exerts on different aspects of people management, it remains the missing stakeholder in the HRM literature. In this paper, we take stock of previous research, and conclude that it is scarce and lacks consolidation. On the basis of our findings, but also thinking in terms of what is still missing, we develop a conceptual framework that may guide further research, advocating for the need to consider co-evolutionary approaches in an attempt to integrate selection and adaptation perspectives, as well as multi-level and multi-actor factors. Future work should systematically address and distinguish top management characteristics from top management agency and link these more clearly to a diversity of HRM dimensions. By doing so, scholars will help to firmly incorporate the role of top management in the research agenda of HRM and pursue different avenues that can be scientifically sound as well as practically relevant.